2004
DOI: 10.1038/sj.bjc.6601742
|View full text |Cite
|
Sign up to set email alerts
|

Stage and treatment variation with age in postmenopausal women with breast cancer: compliance with guidelines

Abstract: Breast cancer-specific mortality is static in older women despite having fallen in younger age groups, possibly due to lack of screening and differences in treatment. This study compared stage and treatment between two cohorts of postmenopausal women (55 -69 vs 470 years) in a single cancer network over 6 months. A total of 378 patients were studied (470: N ¼ 167, 55 -69 years: N ¼ 210). Older women presented with more advanced disease (470: metastatic/locally advanced 12%, 55 -69 years: 3%, Po0.01). Those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
106
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 28 publications
6
106
1
3
Order By: Relevance
“…With dementia predominantly affecting the elderly, this represents a significant problem in this population. Studies show that older patients with dementia are less likely to receive standard cancer therapies [12] and that this is often stated as a reason for selecting PET over surgery [6,39]. However, there are currently no guidelines for the treatment of operable breast cancer in this complex group of patients which may reflect the lack of consensus amongst HCPs surveyed here.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…With dementia predominantly affecting the elderly, this represents a significant problem in this population. Studies show that older patients with dementia are less likely to receive standard cancer therapies [12] and that this is often stated as a reason for selecting PET over surgery [6,39]. However, there are currently no guidelines for the treatment of operable breast cancer in this complex group of patients which may reflect the lack of consensus amongst HCPs surveyed here.…”
mentioning
confidence: 54%
“…Consequently, older patients with operable breast cancer may be offered alternative treatment modalities, such as primary endocrine therapy (PET) [5,6], where oestrogen receptor (ER) positive disease is treated with endocrine therapy alone. A meta-analysis comparing PET with surgery found no difference in survival, although rates of local control were inferior with PET [7], which may necessitate a change in management [8,9].…”
mentioning
confidence: 99%
“…Furthermore a recent study demonstrated a lack of consensus among HCPs regarding the optimal way to treat this group [12]. Older patients with dementia are less likely to receive standard cancer therapies [28] and this is often stated as an explanation for selecting PET over surgery [5,29].…”
Section: Resultsmentioning
confidence: 99%
“…Older patients have higher rates of comorbidity and frailty so that the risk of death from breast cancer is relatively reduced, with only 23% deaths due to breast cancer for patients diagnosed in their mid-80s compared to 73% for patients diagnosed in their 50s [3]. Older patients with operable breast cancer may be offered alternative treatment modalities, such as primary endocrine therapy (PET) [4,5], wherein oestrogen receptor (ER) positive disease may be treated with endocrine therapy alone.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, its use is widespread, with up to 42% of all women over 70 being treated in this way, regardless of whether co-morbidity is documented (Wyld et al, 2004).…”
mentioning
confidence: 99%